Pemberdayaan Ekonomi Pemuda Melalui Pelatihan Shopee Affiliate Berbasis Konten Kreatif Digital di Kelurahan Kebumen - Muhammad Afif Aldi; Muhammad Al Ghaniy Akbar; Danny Herawan (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2026)
The limited utilization of digital technology and social media by village-level youth remains a major obstacle to creating independent economic opportunities. This community service initiative aims to enhance the digital skills and creative economic income of Karang Taruna members through the optimization of the Shopee Affiliate program. The activity was conducted on Tuesday, June 30, 2026, in partnership with Kebumen Village, involving 30 Karang Taruna members. The methods employed included socialization, counseling, workshops, demonstrations, hands-on practice, and discussions. Direct evaluation was carried out using pre-test and post-test questionnaires to measure participants' competence. The results indicated that the program ran smoothly and yielded a significant impact. There was a 75% surge in participants' hard skills regarding trending product research, custom link techniques, and digital content creation. Furthermore, 85% of the participants now possess active, verified affiliate accounts and are prepared to generate economic value independently post-training without relying on product stock capital.